Perancangan Sistem Informasi Pemesanan Jasa Renovasi Bangunan Berbasis Web Untuk Peningkatan Efektivitas Layanan Pada CV. Sejahtera Kita - Afiani Agus Abdillah; Cahyono, Adi; Arfandi Lubis, Danish; Hakim, Luqman (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
CV. Sejahtera Kita is a company engaged in building renovation services, room renovation services, and custom furniture manufacturing. In its business processes, service ordering activities are still carried out manually through direct communication and instant messaging applications, resulting in several problems such as difficulties in managing customer data, delays in delivering project information, and ineffective monitoring of ongoing work. The purpose of this study is to design and develop a Web-Based Building Renovation Service Ordering Information System that can assist the company in managing service ordering processes in an integrated manner. The system development method used is the Software Development Life Cycle (SDLC) with the Waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The system was developed using the Next.js framework and MySQL database. This study resulted in a web-based application that provides customer registration, renovation service ordering, order management by administrators, project monitoring by supervisors, and real-time project status tracking for customers. The developed system is capable of improving service effectiveness, accelerating data processing, simplifying project management, and enhancing communication between customers and the company.